Modified Two-Stage Exchange for MRSA Periprosthetic Joint Infection in Total Knee Arthroplasty: Case Report - RMSN, Magetsari; Mulyadi, Dicky (Indonesian Hip and Knee Society (IHKS), 2023)
Periprosthetic joint infection (PJI) of the knee is a catastrophic complication that occurs in 1-2 % of patients after total knee arthroplasty. As the number of primary knee arthroplasty procedures increases, thus will the number of periprosthetic infections continues to be a major challenge with a significant financial burden and physical and psychological morbidity for patients. This report presents a case of MRSA Periprosthetic joint infection in TKA with a two-stage exchange as a treatment. A 79-year-old woman had a painful, swollen knee with a sinus tract with purulent discharge at her left knee. The KSS Knee Score was 25, and the Function Score was 15. According to the findings, the patient was diagnosed with Periprosthetic Joint Infection by the Modified MSIS criteria and underwent a two-stage revision surgery with rifampicin and ciprofloxacin antibiotic administration. PJI is a rare complication, with more than 50% of the cases caused by gram-positive cocci, Staphylococcus coagulase-negative, and Staphylococcus aureus. The treatment of PJI must be tailored according to the patient's clinical characteristics. Prosthesis exchange in one or two stages is the first choice of procedure. Two-stage revision surgery for knee PJI with dual antibiotics of rifampicin and ciprofloxacin is adequate to control infection and reinfection in a one-year follow-up.